Keep them coming back: The role of variety and aesthetics in institutional food satisfaction - Carins, Julia Elizabeth; Rundle-Thiele, S.R.; Ong, Derek Lai Teik * (Elsevier, 2020)
Institutional food service settings can deliver higher levels of support for healthy eating; yet institutional food outlets are not a customer favorite. Changing food service provisioning within institutional settings is likely to create expectations for a more enjoyable experience and improve diner satisfaction, which in turn can foster increases in attendance. This study modified the food servicescape in a military dining setting, by changing the physical setting (or servicescape), variety and presentation of foods, and examined the impact of changes on customer satisfaction. Using a cross-sectional pretest/posttest survey design with (n = 421) diners, followed by modelling with PLS-SEM, a strong relationship was found between food variety and satisfaction; and a moderate relationship between facility aesthetics and satisfaction. These predictors explained 58% of variance in satisfaction. This study shows how diner satisfaction can be improved in institutional food service outlets; providing a demonstration of the impact of food servicescape changes in a real-world institutional food setting.